Kryteria klasyfikacji leasingu na gruncie prawa bilansowego, podatkowego i cywilnego - Janczyk-Strzała, Elżbieta (Criteria of Leasing Transactions Classification on the Field of Tax Law, Accounting Law and Civil Law, 2005)
Leasing regulations in Polish law are quite new and complicated. Due to the rapid growth of transactions made and adjusting Polish Law to the EU legal regulations, significant leasing regulations have been introduced. The same agreement can be treated in a different way by different regulations. This article focuses on the criteria of classification of leasing transactions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 342-346